(untitled) (Italian Journal of Public Health, 2006)
Public health genomics unifies the scientific disciplines of genetics and public health. Public health genomics aims to facilitate the transfer of newly acquired knowledge in genetic and molecular biology into classical med- icine, to evaluate the currently available genetic tests, and to educate both the medical community and the gen- eral population about advancements in molecular and cell biology of medical interest. Due to various factors, the application of new genetic discoveries in classical medicine and the evaluation of the current genetic clini- cal tests occur at relatively slow paste. The challenge of public health genomics is to create the most effective modus for coexistence of new molecular and cell biology discoveries and classical medical techniques in applied medicine. The ultimate goal is to accomplish a truly individualized medical therapy.